PRIRATE 2020 guidelines for reporting randomized trials in Endodontics: a consensus‐based development. (23rd April 2020) - Nagendrababu, V.; Duncan, H. F.; Bjørndal, L.; Kvist, T.; Priya, E.; Jayaraman, J.; Pulikkotil, S. J.; Pigg, M.; Rechenberg, D. K.; Væth, M.; Dummer, P. M. H.
Abstract: In evidence‐based health care, randomized clinical trials provide the most accurate and reliable information on the effectiveness of an intervention. This project aimed to develop reporting guidelines, exclusively for randomized clinical trials in the dental specialty of Endodontology, using a well‐documented, validated consensus‐based methodology. The guidelines have been named Preferred Reporting Items for RAndomized Trials in Endodontics (PRIRATE) 2020. A total of eight individuals (PD, VN, HD, LB, TK, JJ, EP and SP), including the project leaders (PD and VN) formed a steering committee. The committee developed a checklist based on the items in the Consolidated Standards of Reporting Trials (CONSORT) guidelines and Clinical and Laboratory Images in Publications (CLIP) principles. A PRIRATE Delphi Group (PDG) and PRIRATE Face‐to‐Face Meeting group (PFMG) were also formed. Thirty PDG members participated in the online Delphi process and achieved consensus on the checklist items and flowchart that make up the PRIRATE guidelines. The guidelines were discussed at a meeting of the PFMG at the 19th European Society of Endodontology (ESE) Biennial congress, held on 13 September 2019 in Vienna, Austria. A total of 21 individuals from across the globe and four steering committee members (PD, VN, HD and LB) attended the meeting. As a consequence of the discussions, the guidelines were modified and then piloted by several authors whilst writing a manuscript. The PRIRATE 2020 guidelines contain a checklist consisting of 11 sections and 58 individual items as well as a flowchart, considered essential for authors to include when writing manuscripts for randomized clinical trials in Endodontics.